Fear of Falling and Physical Activities: A Comparison Between Rural and Urban Elderly People - Mohammad Mahdi Mohammadi; Farhad Azadi; Mohsen Vahedi; Zahra Mahdiin (University of Social Welfare and Rehabilitation Sciences, 2024)
Objective Proper physical activities play an important role in reducing disease and mortality in old age, and is one of the main causes of active aging; however, the fear of falling is a barrier to having proper physical activity. Due to the difference between the elderly living in urban and rural areas regarding the risk factors of fear of falling and the amount and type of physical activity, this study aims to investigate and compare the fear of falling, physical activity, and activities of daily living (ADL) in the elderly living in urban and rural areas of Konarak County, Iran. Materials & Methods In this analytical cross-sectional study, 350 elderly people  aged ≥60 years, who were under the coverage of comprehensive rural and urban health service centers in Konarak, Sistan and Baluchestan province (224 from rural areas and 126 from urban areas) were selected using a random sampling method and based on the inclusion and exclusion criteria. In addition to recording their demographic information, their fear of falling, physical activity, and ADL were measured by the Persian version of falls efficacy scale-international (FES-I), Rapid Assessment of Physical Activity (RAPA), ADL scale, and Instrumental ADL scale (IADL), respectively. Results The mean overall age of the elderly was 68.48±7.84 years (69.53±8.29 years in the rural group and 66.62±6.61 years in the urban group), and there was a significant difference between the two groups in terms of age (P<0.001). Pearson correlation test results showed that the FES-I score had a statistically significant negative relationship with the scores of ADL, IADL, and RAPA1 in total and in each group (P<0.001), but there was no statistically significant relationship between the FES-I score and the RAPA2 neither in total (P=0.40) and nor in rural (P=0.38) and urban (P=0.81) groups. Conclusion The fear of falling is significantly higher in the elderly living in rural areas of Konarak county compared to those living in urban areas. The RAPA1 and basic ADL of the elderly living in urban areas are higher compared to those living in rural areas, but there is no significant difference between them in RAPA2 and IADL. In addition, fear of falling has a significant relationship with physical activity of the elderly in overall and in rural and urban groups.